Telling Stories: Martha Stutz by Javier Daulte - Magnarelli, Sharon (Latin American Theatre Review, 2001)
Assuming a postmodern stance, Martha Stutz (1995) by Argentine playwright Javier Daulte challenges the authority of narrative as it juxtaposes a child’s narrative, Alice’s Adventures in Wonderland, with the juridico-journalistic narrative of a child’s disappearance (Martha Stutz in Córdoba in 1938). The dramatic action of the play is precisely that of telling and performing stories over and over again, as characters struggle for narrative dominance and the power to impose their version of events. Although ostensibly modeled on the detective story genre, the play’s insistence on repetition, particularly the repetition of words and stories, precludes the closure we generally associate with that genre. Instead, the play underscores the capacity of language and narrative to cover over, conceal disappearance and absence. In spite of all the narratives proferred, "Martha" remains a terrifying, inexplicable absence. (SM)